Effects of process conditions on the ultrasonic extraction of phenolics scavenger from Curcuma caesia rhizome - Jemain, Siti Fathimah Putery; Jamal, Parveen; Ahmad Raus, Raha; Amid, Azura; Jaswir , Irwandi (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Malaysian Curcuma caesia has not been studied extensively, even though it has been used as a traditional remedy. This study examined the effects of various extraction temperatures (30, 40, 50, 60, 70 ⁰C) using a high frequency (40kHz) ultrasonic extraction method, time (30,60,90 and 120 minutes), pH (1,2,3,4,5,6,7,8,9,10) on the extraction yield of total phenolics and DPPH scavenging activities from C. caesia rhizome. Extraction was most efficient at pH 6.0, while an extraction time of 30 minutes and temperature of 60⁰C was the best in terms of total phenolics content and DPPH scavenging activity. This study is important due to its ability to improve extraction of total phenolics compound using ultrasonic extraction method while maintaining a relatively high DPPH scavenging activity of the extracts.